Clinical diagnosis and therapeutic approach for stomatitis in an albino-reticulated python (Malayopython reticulatus) at Gembira Loka Zoo, Yogyakarta, Indonesia - Panggalih, Ketawang Enggar; Dewantara, Ragaluh; Khairani, Shafia; Kusuma, Randy (ARSHI Veterinary Letters, 2024)
This case report highlights effective treatment strategies for stomatitis in reticulated pythons, providing valuable insights into veterinary care in reptile conservation. Albino-reticulated pythons (Malayopython reticulatus) play a crucial role in maintaining ecological balance as predators, making their health essential for conservation. At Gembira Loka Zoo, Yogyakarta, Indonesia, an albino python was reported by the zoo keeper to have been off feed for approximately 1-2 months. An attending veterinarian from the reptile unit conducted a thorough examination, revealing inflammation in the mouth and mucosal tissue, along with missing teeth. The affected tooth was extracted to prevent further aggravation of the condition. Treatment included the application of an antiseptic spray containing 0.2% chlorhexidine digluconate and Oxyfresh Dental Gel to the inflamed areas of the mouth. Additionally, supportive therapy with Hematodin was administered. Python showed significant improvement after nine days of treatment, with reduced inflammation and a gradual return to health.